Exploitation of Nanoindentation and Statistical Tools to Investigate the Behavior of Materials - Aminallah, L.; Habibi, S. (Engineering, Technology & Applied Science Research, 2016)
The determination of the performance of materials requires the characterization of materials at scales: macro, micro and nanoscale. Among the most common experimental methods one can find the instrumented indentation test for determining the contact stiffness and contact depth and analyzing the characteristic curve by nanoindentation load on the penetration of the indentor. Through statistical processing of the experimental results, the rigidity of contact on the contact depth is investigated, depending on the indentation load, for bronze, brass and copper. A mathematical model is adopted to describe the polynomial regression by the method of least squares growth rigidity with one or more geometric parameters representative of the size of the footprint. This study allows us to identify factors that influence the rigidity of the materials examined and the sensitivity of the used indenters.